Emerging innovations in wireless networks and broadband technologies - Chilamkurti, Naveen (A volume in the advances in wireless technologies and telecommunication (AWTT), 2016)
This book is a pivotal reference source for the latest scholarly research on the various applications and functionality of wireless technologies, highlighting critical issues relating to network optimization and efficiency.